From private to public governance: The case for reconfiguring energy systems as a commons. (December 2020) - Giotitsas, Chris; Nardelli, Pedro H.J.; Kostakis, Vasilis; Narayanan, Arun
Highlights: The development of energy solutions is stymied by capitalist political and economic imperatives. A novel socio-economic arrangement can germinate alternative technological trajectories. A commons-oriented technical approach for energy production is proposed. Abstract: The discussions around the unsustainability of the dominant socio-economic structures have yet to produce solutions to address the escalating problems we face as a species. Such discussions, this paper argues, are hindered by the limited scope of the proposed solutions within a business-as-usual context as well as by the underlying technological rationale upon which these solutions are developed. In this paper, we conceptualize a radical sustainable alternative to the energy conundrum based on an emerging mode of production and a commons-based political economy. We propose a commons-oriented Energy Internet as a potential system for energy production and consumption, which may be better suited to tackle the current issues society faces. We conclude by referring to some of the challenges that the implementation of such a proposal would entail.